2011
DOI: 10.1016/j.neuropsychologia.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

How emotion leads to selective memory: Neuroimaging evidence

Abstract: Often memory for emotionally arousing items is enhanced relative to neutral items within complex visual scenes, but this enhancement can come at the expense of memory for peripheral background information. This ‘trade-off’ effect has been elicited by a range of stimulus valence and arousal levels, yet the magnitude of the effect has been shown to vary with these factors. Using fMRI, this study investigated the neural mechanisms underlying this selective memory for emotional scenes. Further, we examined how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 41 publications
3
42
0
Order By: Relevance
“…Conversely, very strong memories can integrate into schemata with which they overlap only minimally at the outset because they are unlikely to decay before new associative linkages have been formed. This explains why schemata can be disproportionately influenced by especially strong memories [35][36][37].…”
Section: [ ( F I G U R E _ 2 ) T D $ F I G ]mentioning
confidence: 99%
“…Conversely, very strong memories can integrate into schemata with which they overlap only minimally at the outset because they are unlikely to decay before new associative linkages have been formed. This explains why schemata can be disproportionately influenced by especially strong memories [35][36][37].…”
Section: [ ( F I G U R E _ 2 ) T D $ F I G ]mentioning
confidence: 99%
“…1) and the visual converting process (dorsal and ventral stream, inferior temporal cortex, Fig. 3, no. 2), a representation of the environment is built in the hippocampus, modulated by attention (Hölscher et al, 2003) and emotion (Waring and Kensinger, 2011).…”
Section: Encoding Of Environmental Information In the Perception And mentioning
confidence: 99%
“…They showed that there can be enhanced memory for an emotional focus at the expense of memory for the background context, which is important in place perception and memorising. When engaged during visual scene processing, there is evidence that an association between the encoding process and the likelihood of the trade-off exists in the memory (Waring and Kensinger, 2011). The emotion loaded context has also been investigated by Aviezer et al (2011).…”
Section: The Role Of Attention and Emotion In The Encoding Processmentioning
confidence: 99%
“…Some researchers propose that emotion enhances source memory by increasing overall attention and prioritizing binding of emotional items to their contexts (Hadley & MacKay, 2006;Revelle & Loftus, 1992).However, others suggest attentional trade-off between central emotional items and peripheral contextual details (Easterbrook, 1959;Laney, Campbell, Heuer, & Reisberg,2004), which could compromise memory encoding and binding in emotional situations (Payne, Nadel, Britton, & Jacobs, 2004;Waring & Kensinger, 2011), resulting in impaired source memory.…”
Section: Introductionmentioning
confidence: 99%